2021
DOI: 10.3390/agriculture11090894
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Feeding Hens a Peanut Skin-Containing Diet on Hen Performance, and Shell Egg Quality and Lipid Chemistry

Abstract: Peanut skins are a considerable waste product with little current economic value or use. We aimed to determine the dietary effects of peanut skins on layer production performance and egg quality and chemistry of the eggs produced. Two hundred commercial hens were randomly assigned to four treatments (five replicates) and fed ad libitum for 8 weeks: conventional control diet, diet containing 24% high-oleic peanut (HOPN), diet containing 3% peanut skin (PN Skin), and a diet with 2.5% oleic acid (OA). Hens fed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
(45 reference statements)
0
8
1
Order By: Relevance
“…Secondly, we aim to determine the effects of feeding a whole-in-shell peanut diet or unblanched peanut diet on the quality, lipid and fatty acid content of the eggs produced. In our previous layer feeding trials, we demonstrated that layer body weight, and feed intake of hens fed a 24% unblanched peanut diet was similar to that of hens fed a non-conventional control diet containing soy protein isolate, defatted soybean meal, and yellow corn [3]. However, hens fed a 24% unblanched peanut diet produced a significantly fewer total number of eggs compared to hens fed a control diet containing soy protein isolate [3].…”
Section: Introductionmentioning
confidence: 64%
See 4 more Smart Citations
“…Secondly, we aim to determine the effects of feeding a whole-in-shell peanut diet or unblanched peanut diet on the quality, lipid and fatty acid content of the eggs produced. In our previous layer feeding trials, we demonstrated that layer body weight, and feed intake of hens fed a 24% unblanched peanut diet was similar to that of hens fed a non-conventional control diet containing soy protein isolate, defatted soybean meal, and yellow corn [3]. However, hens fed a 24% unblanched peanut diet produced a significantly fewer total number of eggs compared to hens fed a control diet containing soy protein isolate [3].…”
Section: Introductionmentioning
confidence: 64%
“…In our previous layer feeding trials, we demonstrated that layer body weight, and feed intake of hens fed a 24% unblanched peanut diet was similar to that of hens fed a non-conventional control diet containing soy protein isolate, defatted soybean meal, and yellow corn [3]. However, hens fed a 24% unblanched peanut diet produced a significantly fewer total number of eggs compared to hens fed a control diet containing soy protein isolate [3]. Furthermore, eggs produced from hens fed a 24% unblanched peanut diet were significantly smaller in weight compared to eggs produced from hens fed a control diet containing soy protein isolate [3].…”
Section: Introductionmentioning
confidence: 65%
See 3 more Smart Citations